A Descriptive Analysis of Factors Leading to a 1-Year Remission in Bipolar Disorder. Issue 5 (September 2015) - Rapport, Daniel; Kaplish, Dheeraj; McGrady, Angele; McGinnis, Ronald; Whearty, Kary; Thomas, Manju; Fine, Thomas
<x xml:space="preserve">Abstract</x> Background: Bipolar spectrum disorders are associated with symptomatic and functional disability in many patients. Other studies have examined predictors of outcome with variable results. The goal of this retrospective study was to identify medications associated with a minimum of 12 consecutive months of symptomatic, functional, and syndromal remission. Methods: The charts of 121 patients with confirmed bipolar disorder were reviewed. Data on medical regimen and demographic and adherence factors were gathered using standardized data collection sheets approved by the University of Toledo Institutional Review Board. The criterion for improvement was set at 12 consecutive months of Clinical Global Impressions Improvement ratings of ⩽2, which is a far higher standard of syndromal and functional remissions than the usual 8 consecutive weeks used by the Diagnostic and Statistical Manual of Mental Disorders, 4th Edition, Text Revision. Results: In this sample of 121 patients, 43.8% achieved a minimum of 12 consecutive months of remission, whereas 56.2% did not. When bipolar disorder was divided into its subtypes, 45.5% of our cohort were diagnosed with bipolar I disorder, 27.3% were diagnosed with bipolar II disorder, and 27.3% were diagnosed with bipolar disorder, not otherwise specified. Of the 55 patients with bipolar I disorder, 27 remitted and 28 did not. Of the 33 patients with bipolar II disorder, 12 remitted and 21 did not. Of the 33 patients with bipolar disorder, not otherwise specified, 14 remitted and 19 did not. The treatment regimen that was most closely associated with remission was a combination of atypical antipsychotics (primarily aripiprazole), mood stabilizers (primarily lamotrigine), and an antidepressant. In addition, the patients who achieved remission were more likely to be adherent to medication and with appointments. Conclusions: The chart review showed that 12 consecutive months of symptomatic remission was achieved in our clinic in 43.8% of patients with bipolar disorder when they were treated with tailored medication regimens. The remainder (56.2%) failed to achieve 12 consecutive months of remission based on real-time Clinical Global Impressions Improvement ratings. The combination of an atypical antipsychotic, a mood stabilizer, and an antidepressant was highly correlated with 1-year remission.